Dilemmas in and Pathways to Transboundary Water Cooperation between China and India on the Yaluzangbu-Brahmaputra River - Yan Feng (Water, 2019)
The Yaluzangbu-Brahmaputra River is a hotspot for the discussions on regional security. The interactions on water between China and India are key to realizing water-related 2015 Sustainable Development Goals (SDG) targets in the basin. Using a series of secondary literature information, and the method of event studies, we created a timeline of the Sino-Indian relation events since the 1950s, analyzed the correlations among the contents, the duties by each side, the events of water cooperation, and the diplomatic events between them. We found the following dilemmas hamper water cooperation: (1) The scopes of, and steps towards, transboundary water cooperation are hampered by patchy Sino-Indian diplomatic relations; and (2) there is a lack of motivation for China to cooperate with India without benefits sharing, given that China has undertaken more duties and has often received negative feedback. However, we also found the following pathways toward improving water cooperation: (1) A national cooperation mechanism on transboundary rivers has been established, which may be beneficial for further water cooperation; and (2) a channel for interdisciplinary dialogue should be encouraged to bridge the disparate outlooks and improve interactions between policymakers and scientific experts.